Spectres: When Fashion Turns Back - Clark J. Judith (London, London College of Fashion, 2004)
Published to coincide with a groundbreaking exhibition opening at the brand-new Mode Museum, or MoMu, in Antwerp, and traveling to the V&A in London, Spectres addresses the relationship of contemporary fashion to history, creating a collage of visual references that offer a fascinating insight into the origins of current themes such as alienation, trauma, and phantasmagoria. Details of historic dress and images of 19th-century fairground architecture lead into the work of contemporary designers such as Viktor and Rolf, Alexander McQueen, Hussein Chalayan, Christian Lacroix, and Shelley Fox. In addition, the book describes the exhibition installation, which draws on a skeletal early industrial/metropolitan aesthetic to remind us of its historical connections. Also reproduced are commissioned designs for a giant shadow lantern by the New York fashion illustrator Ruben Toledo. AUTHOR BIO: Judith Clark is a V&A/London College of Fashion Fellow in the V&A"s research department.She was a contributor to the V&A"s Radical Fashion.